Internet use and electronic gaming by children and adolescents with emotional and behavioural problems in Australia – results from the second Child and Adolescent Survey of Mental Health and Wellbeing. (December 2016) - Rikkers, Wavne; Lawrence, David; Hafekost, Jennifer; Zubrick, Stephen
Abstract Background Concerns have been raised of a potential connection between excessive online activity outside the academic realm and increased levels of psychological distress in young people. Young Minds Matter: the second Australian Child and Adolescent Survey of Mental Health and Wellbeing provides estimates of the prevalence of online activity and allows an exploration of associations between this activity, a range of mental disorders, socio-demographic characteristics and risk taking behaviour. Methods Based on a randomized nationally representative sample, a household survey of mental health and wellbeing (Young Minds Matter) was conducted in 2013-14. Interviews were conducted with 6, 310 parents and carers of 4–17 year-olds (55 % response rate), together with self-report questionnaires completed by 2, 967 11–17 year-olds in these households (89 % response rate). The survey identified a range of mental disorders and emotional problems using a variety of diagnostic tools, with the self-report including questions about use of the Internet and electronic games. Five behaviours were measured related to this activity, with 'problem behaviour' being defined as exhibiting at least four out of five behaviours. Results Levels of Internet use (98.9 %, CI 98.5–99.3 %) and electronic gaming (85.3 %, CI 83.9–86.6 %) were high, and 3.9 % (CI 3.2–4.6 %) of young people reported problem behaviour. The proportion of girls with very high levels of psychological distress and problem behaviour (41.8 %, CI 28.8–54.9 %) was twice that for boys (19.4 %, CI 7.7–31.1 %). Those engaging with a range of risk factors reported higher prevalence of problem behaviour than others. Youth who suffered from emotional problems or high levels of psychological distress spent the most time online or playing games. Multivariate analysis showed associations with problem behaviour and having attempted suicide, experiencing high to very high levels of psychological distress, using alcohol, and living in a poorly functioning family. It was not possible to determine the direction of the associations. Conclusion There are links between problem behaviours associated with Internet use and electronic gaming, and mental disorders and risk-taking behaviour in young people. Further studies are required to determine whether these are precursors or sequelae.